The Influence of Work Discipline and The Work Environment on Work Productivity with Motivation As A Moderating Variable on CV Requel HFS Medan - Simanjuntak, Hendra Forwanto; Rahayu, Sri (Action Research Literate, 2026)
This study aims to analyze the influence of work discipline and work environment on employee work productivity with motivation as a moderating variable in CV Requel HFS Medan. The background of this research departs from the phenomenon of declining employee productivity which is characterized by delays in completing work, high attendance rates, and declining work morale in the company environment. The research method used is a quantitative method with a survey approach. Data was collected through a questionnaire distributed to all employees of CV Requel HFS Medan with a sample of 50 respondents determined using saturated sampling techniques. Data analysis is carried out with the help of SmartPLS software version 4.0. The results of the study show that work discipline has a positive and significant effect on work productivity, as well as the work environment has a positive influence on productivity. Meanwhile, motivation has been proven to be able to strengthen the relationship between work discipline and the work environment on employee work productivity. Work Discipline (X1) has a positive effect on Work Productivity (Y), with a path coefficient value (Original Sample column) of 0.891, and significantly, with a P-Values value = 0.000 (Accepted Hypothesis), with aModeration value of 1 (X1) has a positive effect on Work Productivity (Y) through Motivation (Z) as a moderating variable with a path coefficient value (Original Sample column) of 1.399, with a P-Values value = 0.000 (Hypothesis Accepted), eeffect Moderation 2 (X2) has a positive effect on Work Productivity (Y) through Motivation (Z) as a moderating variable with a path coefficient value (Original Sample column) of 1.297, with a value of P-Values = 0.000 (Accepted Hypothesis), the Work environment (X2) has a positive effect on Work Productivity (Y), with a path coefficient value (Original Sample column) of 0.955, with a value of P-Values = 0.000 (Accepted Hypothesis), mMotivation (Z) has a positive effect on Work Productivity (Y) with a path coefficient value (Original Sample column) of 0.917, with a P-Values value = 0.000 (Accepted Hypothesis). These findings indicate that the higher the level of discipline and the quality of the work environment, the more employee productivity will increase, especially if it is supported by high work motivation. This research is expected to be an input for the management of CV Requel HFS Medan in improving the performance and effectiveness of human resources through the management of discipline, work environment, and motivation on an ongoing basis.